Prevalence and risk factors of Type 2 diabetes in an urbanizing rural community of Bangladesh - Islam, M Akhtarul; MMR, Khan; Basak, PM; Khanam, MM; Masum, AA (TAJ: Journal of Teachers Association, 2018)
This cross-sectional study was carried out to estimate the prevalence of type 2 diabetes mellitus and its’ risk factors in an urbanizing rural community of Bangladesh. This study was carried out in my private practice chamber at Rohonpur, Chapai Nawabgonj District of Bangladesh. Rohonpur is an unbanning rural community of Bangladesh. Total 975 subjects (>20 years), were included following simple random procedure. This study was carried out in between 1st July2015 to 31st December 2016. Capillary blood glucose levels, fasting blood glucose (FBG) levels and 2- hour after 75 g oral glucose load (OGTT) were measured. Height, weight, waist and hip circumferences and blood pressure were measured. The study population was lean with mean body mass index (BMI) of 20.48. The total prevalence of type 2 diabetes was 8.5%, men showed higher prevalence (9.4%) compare to women (8.0%). Increasing age and higher BMI were found to be significant risk factors following both FBG and OGTT. The study has shown that prevalence of diabetes has increased in the populations who are in transitional stage of urbanization, and may indicate an epidemiological transition due to fast expanding urbanization. TAJ 2016; 29(2): 26-30